MAPPING OF RESEARCH PRODUCTIVITY IN SRM UNIVERSITY: A SCIENTOMETRIC STUDY - R, Senthilkumar; G, Ulaganathan (Kongunadu Research Journal, 2017)
This paper discusses about the published research articles and its citation available in the Indian Citation Index by the authors from SRM University. The relevant data are collected from Indian Citation Index and it was analyzed. It shows among the 510 articles, the maximum of 157(30.78%) articles published in 2015 and minimum of 1 (0.20%) articles published in 2005. Based on the citation during the period 153 citations were made. Among the 153 Citations, maximum of 32 (20.92%) citations in 2010 and minimum number of citation 1 (0.65%) in 2006 & 2007, was identified.